ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DALAM MENENTUKAN HARGA JUAL TELUR AYAM PADA UMKM LAYER DI KECAMATAN MA’RANG KABUPATEN PANGKEP - Wahyuningsi; Abd Salam; Ainun Arizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine whether the calculation of the cost of goods manufactured (COGM) for laying hen eggs is accurate in setting a competitive selling price. The research method used is descriptive research with a quantitative approach, intended to analyze the calculation of production costs in determining the selling price of chicken eggs in Micro, Small, and Medium Enterprises (MSMEs). Data collection was conducted through several poultry farm owners located in Pangkep Regency. The results of the study indicate that the calculation of the cost of goods manufactured (COGM) using the full costing method shows differences in cost efficiency levels among the farms. Cahaya Mandiri Farm has the lowest COGM at Rp33,955 per bundle, while Rahmat Farm records a COGM of Rp38,310 per bundle; both remain below and competitive with the market price of laying hen eggs, which ranges from Rp45,000 to Rp50,000 per bundle. In contrast, Rasyid Farm has the highest COGM at Rp65,850 per bundle, resulting in a selling price of Rp79,020 per bundle based on the cost-plus pricing method, making it less competitive in the market